Biomass Waste as Sustainable Raw Material for Energy and Fuels - Clauser, Nicolás Martín (2021)
Sustainable development is the common goal of the current concepts of bioeconomy and circular economy. In this sense, the biorefineries platforms are a strategic factor to increase the bioeconomy in the economic balance. The incorporation of renewable sources to produce fuels, chemicals, and energy, includes sustainability, reduction of greenhouse gases (GHG), and creating more manufacturing jobs fostering the advancement of regional and social systems by implementing the comprehensive use of available biomass, due to its low costs and high availability. This paper describes the emerging biorefinery strategies to produce fuels (bio-ethanol and γ-valerolactone) and energy (pellets and steam), compared with the currently established biorefineries designed for fuels, pellets, and steam. The focus is on the state of the art of biofuels and energy production and environmental factors, as well as a discussion about the main conversion technologies, production strategies, and barriers. Through the implementation of biorefineries platforms and the evaluation of low environmental impact technologies and processes, new sustainable production strategies for biofuels and energy can be established, making these biobased industries into more competitive alternatives, and improving the economy of the current value chains.